Responsible Bureaucracy as a Vehicle for Sustainable Development: Comparing Finland and Nigeria's Civil Services - Odoemene, Robert (My University, 2010)
This study is a historical interpretation and comparison of the civil services of Finland and Nigeria and tries to explain the extent to which the two cases have impacted on the wellbeing of their respective nations and citizenry. The task is achieved by comparing the cultures, structures and functions of the two civil services through an extensive research. The study argues that even though it is generally held that "bureaucracy‟ exists in all political systems, its effects on public administration are felt differently. While some nations have transformed their bureaucracies to become responsible and serve as an agent of national development, others are still running the old traditional type which is believed to retard efficiency and slow down development. Finland actualized sustainable socio-economic development through the strengthening of its bureaucratic institutions and elimination of corruption; education and training of its workforce, reducing hierarchy, and marching rewards with performance. In the case of Nigeria, sustainable development remains far-fetched. Corruption, high power distance and over-staffing are among factors that have hindered efficiency and effectiveness of the Nigerian civil service, and therefore, have derailed the course of socio-political and economic development of the country. However, it is suggested that the civil service could be made responsible if the Nigerian government can adopt a gradual implementation of New Public Management reform. Firstly, infrastructural facilities must be put in place to facilitate quick service delivery. Then, corruption must be fought head on to guarantee public confidence in the management of public affairs, while public agencies should be managed by competent managers. By that, responsible bureaucracy, another term for efficient management would be achieved to encourage sustainable development in the country.
Keywords: fi=Hallintotiede : julkisjohtamisen ohjelma|; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|